If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(x + -1) = 27 Reorder the terms: 2x + 3(-1 + x) = 27 2x + (-1 * 3 + x * 3) = 27 2x + (-3 + 3x) = 27 Reorder the terms: -3 + 2x + 3x = 27 Combine like terms: 2x + 3x = 5x -3 + 5x = 27 Solving -3 + 5x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = 27 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 27 + 3 5x = 27 + 3 Combine like terms: 27 + 3 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 3(1+Y)=3-(5y+2) | | -17=-5+4u | | 2-6x=10-8x | | 4j-1+7= | | 15y=14(y+16) | | 3g+3(-5+4g)=1-g | | 2x^2-7x-16=-3x | | 3x+10=45-2x | | 3(6x-4)=22x | | 3(n-1)-2=4(n-4)-(n-11) | | 2(8q-1)+3(5q+6)= | | 12=2w+2 | | 10(x-5)=9(x+5) | | 9a-4+3a-33=23 | | 2(x-3)+4x=18 | | 5y-5=-35 | | 2(x-3)+4x=6.5 | | 7x-3x-8=24 | | 9y+y+8y+2y+5y= | | 2(x-3)=6.5 | | 3(2x-10)=6(x-10) | | 12x-3=4x+93 | | 3x^2=51x | | 25=4+3y | | 8b-11+3b=121 | | 284-2x=43x+19 | | -2(y-4)=12-y | | 25x^2-49=0 | | c^2=25 | | 5xn-3=32 | | 5(y+2)+3y=50 | | 3t+8t+3t+3t= |